EFFECT OF POULTRY MANURE ON POTATO PRODUCTION UNDER RAINFED CONDITION OF MEGHALAYA - Kumar, Manoj; Gupta, V. K.; Gogoi, M. B.; Kumar, Shantanu; Lal, S. S; Baishya, L. K. (Potato Journal, 2013)
In a field study conducted at Shillong during 2003 and 2004 with poultry manure in combination with inorganic fertilizers, the maximum tuber yield (236 q/ha) was recorded with the application of 100% inorganic fertilizers. The application of 25% poultry manure along with 75% inorganic fertilizers gave tuber yield of 228 q/ha which was at par with 100% inorganic fertilizer treatments, suggesting that 25% inorganic fertilizers may be substituted with poultry manure as organic source without any significant loss in tuber yield. The yield of medium sized (30-50 g) tubers improved with the increasing dose of poultry manure in combination with inorganic fertilizers.